PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SUPLEMEN MUSCLE FIRST - Nurul Hilmiyah; David Al Ghani; Bayu Retno Widyastuti (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2021)
This study aims to determine the effect of price and product quality on purchasing decisions on customers of Muscle First’s fitness supplement products. This study uses a purposive sampling technique. The samples must be the costumer of Muscle First in Padang City who have already made a purchase of the product at least once. There are 100 respondents of this study. The analytical technique used in this study is descriptive analysis and multiple linear regression analysis using a software named SPSS (Statistical Package for the Social Sciences). The results of this study prove that the price variable has a positive and significant effect on purchasing decisions for Muscle First products in Padang City. The product quality variable has a positive and significant effect on purchasing decisions for the purchase of Muscle First products in the Padang City. The price and product quality variables simultaneously have a simultaneous influence on the decision to purchase Muscle First products in the Padang City.